Adaptation des territoires insulaires : éléments de réflexion à partir de deux îles françaises (Ré et la Réunion) - François Bertrand; Elsa Richard (VertigO)
This paper proposes to verify the hypothesis that the adaptation of the island territories would not necessarily be implemented proportionally to the degree of exposure to climatic hazards. After a presentation of the main impacts of climate change which potentially affect, and will affect, small islands, the agenda setting processes and action strategies, deployed by island territories facing the effects of climate change, are analyzed, on the basis of studies, led in 2006 and 2007 on two French islands, a metropolitan one (Ré) and an overseas department (Réunion). Finally, the similarities observed in local-level responses to climate change impacts are highlighted, and the consequences of the adaptation for the principle of territorial solidarity are discussed.